Pemberantasan Pungutan Liar - Herry Indiyah Wismani (Universitas Mahendradatta, 2018)
Illegal charges are unofficial charges and have no legal basis, thereforethey are called illegal fees. In illegal levies, the criminal offenses that have beenimposed have no clear rules. In the absence of clear rules on illegal levies, this willlead to the problem of criminal law itself, especially regarding the issue of criminalliability. Illegal charges of most cases that occur there is an element of abuse ofauthority.In the implementation of the eradication of illegal levies, elements against the laware necessary to determine a person has committed a crime. The governmentestablished Presidential Regulation Number 87 of 2016 on the Task Force of CleanSweep of Illegal Levies to combat illegal levies. But the reality in the practice ofillegal levies is still happening. These illegal charges are just a term in everyday lifeand should be equated with a criminal act of extortion, fraud and corruption. Thecriminal act of illegal levies is felt very disturbing society, because the impact isdirectly felt by the community.The purpose of this study is to provide an explanation of what types of illegal feesare and what the underlying laws of illegal levies are and how to combat illegal feesand by using whatever approaches are used.In this study used literature research and field research. Library research wasconducted to obtain theoretical data, while field research was conducted to obtainprimary data through interviews with informants and respondents. The result of theresearch indicates that the factors causing illegal charges are economic factorswhose purpose is to increase income and the opportunity to conduct illegal leviesdue to weak supervision system, low legal awareness as well as poor stateadministration discipline and abuse of authority.